ONSIM: The Optical Network Simulator for Hybrid Switching Paradigms - Bonani, L. H.; Abbade, M. L.F. [UNESP]; Queiroz, J. C.F. (My University, 2019)
The elastic optical network (EON) was proposed as a solution to avoid the spectrum waste in conventional WDM networks, since it improves the network utilization. However, the elastic optical network is still based on an optical circuit switching (OCS) paradigm, which tends to waste bandwidth resources due to idle times of the reservation process. Hybrid solutions, including the optical packet switching (OPS) paradigm have been proposed in optical networks designed for specific applications, for instance data center optical networks, and offers a better efficiency in the resource usage. Therefore, to allow future studies we present an adaptation of Optical Network Simulator (ONSim) to work on hybrid switching paradigms. As an example, we analyze blocking probability in this context, considering specifically the operation of a hybrid OCS/OPS optical network with different proportions of traffic.
Keywords: optical network simulator; optical switching paradigms